Monoclonal antibody 3H11 chimeric antigen receptors enhance T cell effector function and exhibit efficacy against gastric cancer - Han, Haibo (Oncol Lett, 2018)
Although chimeric antigen receptor T cell (CAR-T) therapies for certain types of solid tumors have been used in clinical trials, novel CARs that are able to target gastric cancer (GC) are still required. In our previous study, monoclonal antibody 3H11 (mAb 3H11), generated from immunization with five human GC cell lines, was demonstrated to have a 93.5% positive reaction with a clear membrane location and more than 5% cancer cell staining in GC tissues in our previous study. In the present study, 3H11-CARs were designed for modified T cell therapy. To begin with, it was confirmed that the single-chain variable fragment (scFV) of the mAb 3H11, known as scFV-3H11, exhibited similar activity with the natural antibody. In addition, scFV-3H11 CAR-T cells are able to kill tumor cells accompanied with increased interleukin-2 and interferon-γ secretion in vitro, and reduced the tumor burden in GC cell lines and patient-derived GC cells in vivo. In conclusion, scFV-3H11 CARs may have the potential to treat mAb 3H11-positive GC.